Falsafah Serat Sastra Gendhing sebagai Basis Kepemimpinan Pendidikan: Philosophy of Serat Sastra Gendhing as a Basis For Educational Leadership - Mahrus, Mahrus; Itqon, Zubdatul (STAI Ma'had Aly Al-Hikam Malang, 2023)
Leadership is a form of art and culture in educational institutions. Leadership practices that tend to adopt leadership styles from the West have developed in the current era of globalization. Like a pearl buried by civilization and developments over time, the use of theories from outside seems to be increasingly sinking the existence of Javanese philosophy. Exploring Javanese leadership philosophy is an effort to revive a leadership philosophy based on local wisdom. It could be that the current leaders have jumped too far from their essential position. Serat Sastra Gendhing is a leadership philosophy that contains seven main mandates that can be upheld by a leader. Mastery of these seven characteristics is a characteristic of ideal leadership. This article was prepared based on library research, because it uses books as a data source. The data collection method is documentation. Meanwhile, the analysis method is content analysis. Serat Sastra Gendhing teaches the need for a leader to have social-spiritual intelligence, defend truth and justice, the ability to develop culture and be a pioneer of science. Kepemimpinan merupakan bentuk kesenian dan kebudayaan dalam tatanan lembaga pendidikan. Praktik kepemimpinan yang cenderung mengadopsi gaya kepemimpinan dari Barat berkembang pada era globalisasi saat ini. Ibarat mutiara yang terkubur oleh peradaban dan perkembangan masa, penggunaan teori-teori dari luar nampaknya semakin menenggelamkan eksistensi falsafah Jawa. Penggalian falsafah kepemimpinan Jawa merupakan upaya untuk mengangkat kembali falsafah kepemimpinan berbasis kearifan lokal. Bisa jadi pemimpin yang ada saat ini telah melompat terlalu jauh dari pijakan esensinya. Serat Sastra Gendhing merupakan falsafah kepemimpinan yang berisi tujuh amanah utama yang dapat dpegang oleh seorang pemimpin. Penguasaan tujuh karakteristik tersebut merupakan ciri kepemimpinan yang ideal. Artikel ini disusun berdasarkan penelitian kepustakaan, karena menggunakan buku-buku sebagai sumber datanya. Metode pengumpulan datanya adalah dokumentasi. Sedangkan metode analisisnya adalah analisis isi. Serat Sastra Gendhing mengajarkan perlunya seorang pemimpin memiliki kecerdasan sosial-spiritual, membela kebenaran dan keadilan, kemampuan mengembangkan budaya dan pelopor ilmu pengetahuan. Kata Kunci: Falsafah, Serat Sastra Gendhing, Kepemimpinan Pendidikan.